Balance and Walking Speed Outcomes in Individuals Receiving Inpatient Rehabilitation for Acute Cerebellar Stroke - Uzair Hammad; Abigail W. Anderson; Emma Scammon; Reid Whiting; Juan Pablo Rodriguez; Rolando T. Lazaro; Morris Casano Beato (Nursing Reports)
Background/Objectives: Cerebellar strokes account for only 2–3% of all strokes occurring annually in the United States but represent a disproportionally higher share of morbidity and mortality. Evidence examining the effect of inpatient rehabilitation on functional outcomes following a cerebellar stroke is limited. This study aimed to examine the effects of inpatient rehabilitation on balance and walking speed in individuals with cerebellar stroke. A secondary purpose of this study was to examine the length of inpatient rehabilitation stay of the included patients. Methods: A retrospective analysis was conducted using review of patient records during their inpatient rehabilitation stay from January 2021 to February 2022 at a large hospital system in the southeast United States. Balance and gait outcomes were examined on admission and discharge from inpatient rehabilitation that included physical therapy interventions. A paired t-test examined for changes in outcomes from admission to discharge. Pearson correlation examined for the association between length of stay and outcomes. Results: A total of 15 records were reviewed. There were significant improvements in the Berg Balance Scale (BBS), Postural Assessment Scale for Stroke (PASS), and the 10-Meter Walk Test (10MWT) (p’s < 0.01) from admission to discharge with large effect sizes (range d = 0.70–1.67) following inpatient rehabilitation. The average length of stay was 12.67 days (SD = 6.5) and the mean total hours of combined occupational, physical, and speech therapy was 27.33 (SD = 6.52) h. There was a moderate association between length of stay and PASS (r = 0.525, p = 0.04) and BBS (r = 0.546, p = 0.04) outcomes. Conclusions: Patients who underwent inpatient rehabilitation following acute cerebellar strokes demonstrated improvements in balance and gait speed. Study results could assist clinicians designing interventions for patients with cerebellar strokes in the inpatient rehabilitation setting.